Розвиток інвестиційної привабливості економіки України в післявоєнний період: стратегічні пріоритети, проблеми та основні вектори їх вирішення. - Атамас, Олександр Петрович; Аtamas, Oleksandr (Державний податковий університет, 2023)
Формування конкурентоспроможної економічної структури суспільства вимагає мобілізації всіх національних ресурсів, максимального використання національних переваг. Однак, поза увагою також не можуть лишатися інвестиційні джерела, що знаходяться за межами країни і здатні посилити трансформаційний ефект. Для окремих національних економік саме масштабна диверсифікаційна міжнародна інвестиційна діяльність визначає базові довгострокові механізми високоінтегрованого економічного розвитку. У статті проаналізовано групи факторів, які визначають ступінь інвестиційної привабливості економіки держави, дані про обсяги інвестиційної діяльності України у період 2002–2023 рр., значення інтегрального індексу інвестиційної привабливості України у період 2018–2022 рр. Крім того, наведено перелік заходів для покращення інвестиційної привабливості економіки України у 2023–2024 рр. The formation of a competitive economic structure of society requires the mobilization of all national resources, the maximum use of national advantages. However, investment sources located outside the country and capable of enhancing the transformational effect cannot be ignored either. Results. For individual national economies, it is the large-scale diversification international investment activity that determines the basic long-term mechanisms of highly integrated economic development. In addition, proper conditions have not yet been created for the creation of a system of information support for the state of development of the investment attractiveness of Ukraine's economy and the disclosure of factors that prevent the acceleration of progressive structural changes in the domestic economy. This prevents the formation of serious foundations for the development of an effective investment business. It is difficult for domestic investment structures to transform into international institutions of joint investment, to contribute to the formation of flows of investment investments in the domestic economy. The article analyzes groups of factors that determine the degree of investment attractiveness of the state economy, data on the volume of investment activity of Ukraine in the period 2002–2023, the value of the integral index of investment attractiveness of Ukraine in the period 2018–2022. In addition, a list of measures to improve the investment attractiveness of Ukraine is given attractiveness of the economy of Ukraine in 2023–2024. One of the dominant elements of Ukraine's development in modern conditions is investment. Conclusion. The state of production, the level of technical equipment of enterprises and the possibility of solving social and environmental problems of the economy depend on the efficiency of their use. The nature of investment processes, their intensity and effectiveness, as well as their management depend on the investment attractiveness formed in the state's economy. Therefore, this issue is strategic for Ukraine.
Development of the investment attractiveness of ukraine's economy in the post-war period: strategic priorities, problems and the main vectors of their solution
Keywords: інвестиційна привабливість; investment attractiveness; розвиток; development; післявоєнний період; post-war period; стратегія; strategy; пріоритет; priority; вектор; vector